10-Gingerol Enhances the Effect of Taxol in Triple-Negative Breast Cancer via Targeting ADRB2 Signaling - Liang Y; Wu G; Luo T; Xie H; Zuo Q; Huang P; Li H; Chen L; Lu H; Chen Q (Dove Medical Press, 2023)
Yuqi Liang,1,2,* Guosong Wu,3,* Tianyu Luo,1,2,* Haimei Xie,2 Qian Zuo,2 Ping Huang,2 Huachao Li,2 Liushan Chen,2 Hai Lu,4,* Qianjun Chen1,2,* 1The Second Clinical College of Guangzhou University of Chinese Medicine, Guangzhou, Guangdong, 510006, People's Republic of China; 2Department of Breast, Guangdong Provincial Hospital of Chinese Medicine, Guangzhou, Guangdong, 510120, People's Republic of China; 3Nanfang Hospital Baiyun Branch, Guangzhou, Guangdong, 510000, People's Republic of China; 4The First People's Hospital of Shaoguan, Shaoguan, Guangdong, 512099, People's Republic of China*These authors contributed equally to this workCorrespondence: Qianjun Chen, Department of Breast, Guangdong Provincial Hospital of Chinese Medicine, 111 Dade Road, Yuexiu District, Guangzhou, 510102, People's Republic of China, Email cqj55@163.com Hai Lu, The First People's Hospital of Shaoguan, No. 3, South Dongdi Road, Shaoguan, 512099, People's Republic of China, Tel +86 15622187291, Email hysa1985@163.comPurpose: Although paclitaxel is widely used in cancer treatment, severe side effects and drug resistance limit its clinical use. 10-gingerol (10-G) is a natural compound isolated from ginger, which displays anti-inflammatory, antioxidant, and antiproliferative properties. However, the chemotherapy-sensitization effect of 10-G on triple-negative breast cancer (TNBC) has not been fully clarified. This study is aimed at investigating the effect of 10-G on the paclitaxel sensitivity in TNBC, and its underlying mechanism.Methods: The study was determined through in vitro and in vivo experiments. Cell viability and proliferation were detected by cell counting kit 8 (CCK-8) and colony formation. To detect cell apoptosis, flow cytometry and TUNEL were used. The expression of proteins was detected by Western blotting and immunohistochemistry. The molecular docking and gene knockout were corroborated by interactions between 10-G and adrenoceptor Beta 2 (ADRB2). The body weight of mice, histopathology and organs (kidney and spleen) coefficients were used to monitor the drug toxicities.Results: In vitro, 10-G increased the sensitivity of TNBC cells to paclitaxel, and could synergistically promote the apoptosis of TNBC cells induced by paclitaxel. In combination with molecular docking and lentivirus knockdown studies, ADRB2 was identified as a 10-G binding protein. 10-G inhibited ADRB2 by binding to the active site of ADRB2. Knockdown of ADRB2 reduces the proliferation activity of TNBC cells but also attenuates the sensitizing effects of 10-G to paclitaxel. Western blotting and immunohistochemistry showed that 10-G played an anti-proliferation and chemotherapy-sensitizing role by inhibiting the ADRB2/ERK signal. Toxicity evaluation showed that 10-G would not increase hepatorenal toxicity with paclitaxel.Conclusion: This data suggests that 10-G may be used as a new chemotherapeutic synergist in combination with paclitaxel to enhance anticancer activity. The potential value of ADRB2 as a target for improving chemotherapy sensitivity was also emphasized.Keywords: triple-negative breast cancer, combined therapies, 10-gingerol, paclitaxel, adrenoceptor Beta 2